Navigating Cultural Hybridity in the 21st Century: New Perspectives and Applications (KULT_online, 2025)
Cultural Identities in a Global World: Reframing Cultural Hybridity engages in a thought-provoking debate on the meaning and place of cultural hybridity in the twenty-first century. The authors in this volume provide their definitions of the concept, rethinking it through theoretical, methodological, and social frameworks to redefine it and open space for the social, political, and cultural entanglements of each society. This book is a must-read for those who seek to find new meanings and applications for this ever-changing concept.